Research on a method for capturing bullets with limited deformation for forensic comparative examination - Pacek, Dawid; Badurowicz, Przemysław; Gieleta, Roman (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
There are currently no solutions that could be effectively used for stopping a wide range of non-full metal jacket bullets without deformation. The paper presents research on the elaboration of a novel solution in the form of a material system combining composite and fluid. It contains a demonstration of the results proving its effectiveness and an analysis of the solutions of bullet traps currently used in forensic laboratories, as well as the system based on a composite structure proposed for the current needs. The experimental tests and the numerical simulations of bullet impact into water, with a nominal velocity, are described. The critical value of impact velocity cr (which does not cause deformation of the bullet) was found numerically. The composite reducing bullet velocity to cr was prepared and tested. With the use of the composite and plasticine, a monolithic hollow point 9 mm GECO Action Extreme bullet was decelerated and slowly stopped in such a manner as not to cause bullet deformation. The proposed method could therefore be used to capture non-full metal jacket bullets in a form facilitating the determination of whether the given weapon was used to fire a projectile of the same type as the one found at the crime scene.